2018
DOI: 10.17694/bajece.419645
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Impact of Team Formation by Introversion/Extraversion in Software Projects

Abstract: Human factors have an important effect on performance of software teams and resulting software products. One of the seldom-studied aspects of human factors is the effect of personality-based team formation on team cohesion and quality of the software product. In this study, we investigate the above effect by conducting an exploratory case study during a term-long undergraduate software engineering course containing a project component with 50 undergraduate students. We grouped the students based on the social-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…& "Customer skill, training and education" and "Customer experience" in the base model are somewhat unclear and overlapping with one another, and as a result, based on reviews (Ahimbisibwe et al 2015) and the relevant literature, we expanded them to "Customer skill, training and education in IT", and "Customer experience in its own business domain" since the two aspect shall be separated as a customer may have a good skill level in one and not in the other. & As a result of our recent research (Karapıçak and Demirörs 2013;Garousi and Tarhan 2018) on studying the need to consider personality types in software team formations, and discussion with and feedback from our industry partners in the course of our long-term industry-academia collaborations (e.g., (Garousi and Herkiloğlu 2016;Garousi et al 2016a;Garousi et al 2016b;Garousi et al 2015a)), we added "Team building and team dynamics" as a new CSF to the 'process' category of project success. Throughout our industrial projects, we have observed many times that one side product of successful projects is the project's influence in positive team building, improving team dynamics (compared to the state before the project), and enhancing team members' opinions about each other.…”
Section: Reviewing and Extending The Csfs Model Of Ahimbisibwe Et Almentioning
confidence: 99%
“…& "Customer skill, training and education" and "Customer experience" in the base model are somewhat unclear and overlapping with one another, and as a result, based on reviews (Ahimbisibwe et al 2015) and the relevant literature, we expanded them to "Customer skill, training and education in IT", and "Customer experience in its own business domain" since the two aspect shall be separated as a customer may have a good skill level in one and not in the other. & As a result of our recent research (Karapıçak and Demirörs 2013;Garousi and Tarhan 2018) on studying the need to consider personality types in software team formations, and discussion with and feedback from our industry partners in the course of our long-term industry-academia collaborations (e.g., (Garousi and Herkiloğlu 2016;Garousi et al 2016a;Garousi et al 2016b;Garousi et al 2015a)), we added "Team building and team dynamics" as a new CSF to the 'process' category of project success. Throughout our industrial projects, we have observed many times that one side product of successful projects is the project's influence in positive team building, improving team dynamics (compared to the state before the project), and enhancing team members' opinions about each other.…”
Section: Reviewing and Extending The Csfs Model Of Ahimbisibwe Et Almentioning
confidence: 99%